DEVELOPMENT AND VALIDATION OF HPLC METHOD FOR SIMULTANEOUS QUANTIFICATION OF VASICINE, GLYCYRRHIZIN AND PIPERINE IN POLY HERBAL COUGH SYRUP - D., SENTHIL RAJAN; G., MURUGANATHAN; SHIVKUMAR, KUMUTAAVALLI; THANGAVEL, GANESH (International Journal of Current Pharmaceutical Research, 2020)
Objective: The present study was undertaken to develop a rapid, simple, specific and economic high performance liquid chromatographic (HPLC) method has been developed, validated and used for simultaneous quantification of Vasicine, Glycyrrhizin and Piperine in poly herbal cough syrup Methods: An Agilent technologies 1200 Series quaternary pump combined with an Agilent 1200 series photo diode array detector (USA), an Agilent 1200 series vacuum degasser (USA) and an Agilent autosampler injector. Chromatographic separation was performed on a Hiber, prepacked column, C18, Size 250x 4.60 mm, 5µ maintained at 25 °C. PJ (solvent A) and HPLC grade Acetonitrile (solvent B). Results: The HPLC developed for quantization was simple, accurate and specific. The drug follows the beer’s lambert’s law in the concentration range of of Vasicine in concentration range 25–250 μg/ml, glycyrrhizin in concentration range 100–1000 μg/ml and Piperine in concentration range of 20–100μg/ml and exhibited good correlation coefficient and excellent mean recovery. Percentage RSD for precision and accuracy of the method was found to be less than 2%. Conclusion: The present standardization provides a specific and rapid tool in the herbal research, permitting to set quality specifications for identity, transparency and reproducibility of these Phytoconsituents in the herbal Cough syrup.